URGENSI FASHĀHAH AL-KALĀM DALAM MENJAGA KEJELASAN DAN KEINDAHAN BAHASA ARAB PERSPEKTIF ILMU BALAGHAH - Nur Intan Sari; M.Nurdin Abdillah (Wahdatul Ulum Institute, 2026)
Fashohatul kalam is a branch of balaghah (argumentary) that discusses the fluency of sentence structure as a benchmark for beauty and clarity of meaning in Arabic. This study aims to examine fashohatul kalam and its three main aspects: tanafur al-kalimat (sentence), dhu'fi al-ta'lif (reference), and ta'qidu salim (speech). The method used is qualitative research with a literature study approach through data collection from classical balaghah books, books, and relevant journals. The results of the study show that fashohatul kalam is a concept that emphasizes the importance of sentences that are well and correctly structured, and free from disharmony in sound, structural weaknesses, and ambiguity in meaning. These three aspects are the main requirements in determining the fluency of a sentence in Arabic. Theoretically, this fluency is closely related to the quality of sentence structure which is able to create clarity of meaning, beauty of expression, and rhetorical power in conveying language.